3D structured optical fiber pressure sensors based on femtosecond laser fabrication - Liu, T; Song, Z; Wang, M; Doyle, CTM; Booth, MJ; Fells, JAJ (Optica Publishing Group, 2023)
Pressure sensors based on air-hole fiber have limitations in design and materials. We fabricate and test pressure sensors with complex 3D structures in commercial fibers, with potential for many types of high-performance fibers.